Cross-Cultural adaptation and validation of the Exercise-Induced Leg Pain questionnaire for Spanish speaking patients. (July 2022) - Castillo-Domínguez, Alejandro; Alvero-Cruz, José Ramón; Páez-Moguer, Joaquín; Nauck, Tanja; Lohrer, Heinz; Scheer, Volker; García-Romero, Jerónimo
Objectives: To cross-culturally adapt and validate a Spanish version of the Exercise-Induced Leg Pain questionnaire. Design: Clinical measurement study. Participants: The validity and reliability of the adapted version were assessed in four groups of 40 patients with exercise-induced leg pain, 40 physically active healthy individuals (control group), 40 athletes with other leg conditions and 40 athletes, military personnel and candidates with no history of injury (risk group). Main measure: Exercise-Induced Leg Pain questionnaire. Reference measures: Spanish version of the Short-Form 36 and Schepsis postsurgical classification scale. Results: In patients with exercise-induced leg pain, the mean age was 24.9 (± 6.7) years and the mean score of the questionnaire was 62.8 (± 10.9). The standard error of measurement and minimum detectable change threshold were 1.67 and 4.63 points, respectively. Excellent internal consistency (Cronbach's α = 0.942) and test-retest reliability (intraclass correlation coefficient = 0.995) were found. The exploratory and confirmatory factor analyses indicated that a one-factor solution explained 66.84% of the variance. For construct validity, 87.5% of the previously stated hypotheses were fulfilled between the total score of the questionnaire and Short-Form 36 dimensions. Concurrent validity, assessed by the Schepsis scale, was almost perfect (r = 0.92, p < 0.001). The predictive validity of the questionnaire was demonstrated using the receiving operating curve (area of 0.992; 95% CI: 0.983–1, p < 0.001). Conclusion: The Spanish version of the Exercise-Induced Leg Pain questionnaire resulted in a reliable and valid instrument to assess patients with exercise-induced leg pain.